A Three-Echelon Dual-Channel Supply Chain Model with Learning Effect Under the Return Policy - Sujata Saha (Department Industrial Engineering, University of Muhammadiyah Malang, 2021)
In today's competitive and technologically developed era, many retailers have adopted an e-channel to increase sales, in addition to the existing traditional retail channel. Although many researchers studied this issue, there is hardly any research that comprehensively considers the learning-effect and return-policy. Therefore, this research aimed to develop an imperfect production dual-channel supply chain model consisting of a supplier, a manufacturer, and a retailer. The manufacturer also has a refurbishment unit adjacent to its production hub, where it reworks all the defectives. The main objective is to maximize the supply chain profit by considering factors, such as inspection error, return policy, and learning-effect of the employees. Finally, this model is analyzed with the Leader-follower relationship strategy and an integrated approach. The research found that the integrated approach is profitable for the entire supply chain, while commodity prices can be minimized. Sensitivity analysis is also presented in this study.